2016
DOI: 10.1002/jca.21518
|View full text |Cite
|
Sign up to set email alerts
|

Plateletpheresis efficiency and mathematical correction of software‐derived platelet yield prediction: A linear regression and ROC modeling approach

Abstract: Trima Accel v6.0 software consistently underestimated PLT yields. Simple correction derived from linear regression analysis accurately corrected this underestimation and ROC analysis identified a precise cut-off to reliably predict a DP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 29 publications
(34 reference statements)
3
18
2
Order By: Relevance
“…A previous report showed a median yield of 5.9 × 10 11 platelets obtained by a Trima Accel v. 6 automated blood collection system. 9 Another report, assessing the performance of the Trima Accel v. 5 automated blood collection system showed a lower platelet yield of 3.85 × 10 11 platelets. 11 In this study, we observed a higher median platelet yield of 6.5 × 10 11 platelets.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous report showed a median yield of 5.9 × 10 11 platelets obtained by a Trima Accel v. 6 automated blood collection system. 9 Another report, assessing the performance of the Trima Accel v. 5 automated blood collection system showed a lower platelet yield of 3.85 × 10 11 platelets. 11 In this study, we observed a higher median platelet yield of 6.5 × 10 11 platelets.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported Pearson's correlation coefficients ranging from 0.496 to 0.802 in univariate models, showing a significant heterogeneity in the reported results across the literature. 9,16,17 It has been reported that the extraction of double platelet products is correlated with slightly longer procedure times, 13 which can be modified by the operator to increase the processed volume of blood and hence increase the platelet yield. For that reason, it is crucial to have good predictive algorithms to accurately adjust the parameters of the apheresis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations